Long-term exposure to a high-fat diet results in the development of glucose intolerance and insulin resistance in interleukin-1 receptor I deficient mice. - MILLS, KINGSTON; FINUCANE, ORLA (My University, 2013)
ABSTRACT Emerging evidence has demonstrated that saturated fatty acids prime pro-IL-1β production and inflammasome-mediated IL-1β activation is critical in obesity-associated insulin resistance (IR). Nonetheless, IL-1 receptor I-deficient (IL-1RI−/−) mice develop mature-onset obesity despite consuming a low-fat diet (LFD). With this apparent contradiction, the present study evaluated whether IL-1RI−/− mice were protected against long-term (6 mo) high-fat diet (HFD)-induced IR. Male wild-type and IL-1RI−/− mice were fed LFD or HFD for 3 or 6 mo, and glucose and insulin tolerance tests were performed. Adipose insulin sensitivity, cytokine profiles, and adipocyte morphology were assessed. The adipogenic potential of stromal vascular fraction was determined. Hepatic lipid accumulation and insulin sensitivity were characterized. IL-1RI−/− mice developed glucose intolerance and IR after 6 mo HFD compared with 3 mo HFD, coincident with enhanced weight gain, hyperinsulinemia, and hyperleptinemia. The aggravated IR phenotype was associated with loss of adipose functionality, switch from adipocyte hyperplasia to hypertrophy and hepatosteatosis. Induction of adipogenic genes was reduced in IL-1RI−/− preadipocytes after 6 mo HFD compared with 3 mo HFD. Obese LFD-IL-1RI−/− mice exhibited preserved metabolic health. IL-1RI−/− mice develop glucose intolerance and IR after 6 mo HFD intervention. While mature-onset obesity is evident in LFD-IL-1RI−/− mice, the additional metabolic insult of HFD was required to drive adipose inflammation and systemic IR. These findings indicate an important interaction between dietary fat and IL-1, relevant to optimal metabolic health.
PUBLISHED
Keywords: saturated fatty acids; Immunology, Inflammation & Infection